Electrolyte additive, electrolyte and battery
By adding lithium compounds containing sulfonate groups and quaternary ammonium groups to the electrolyte of lithium manganate lithium-ion batteries, a stable protective film is formed at high temperature, which solves the problem of poor circulation performance of lithium manganate batteries under high temperature conditions. , significantly improves the battery's high-temperature cycling performance and overall performance.
Patent Information
- Application Number
- CN202411738006.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
AI Technical Summary
Lithium manganate lithium-ion batteries have poor cycling performance under high temperature conditions, mainly due to the structural distortion and manganese dissolution due to the Jahn-Teller effect. The existing electrolyte film-forming additives are easy to decompose at high temperatures and cannot effectively prevent manganese dissolution.
An electrolyte additive is adopted, including a first additive, which is a lithium compound containing a sulfonate group and a quaternary ammonium group, which can form a uniform and dense protective film on the surface of the positive and negative electrode of the battery, prevent the dissolution of manganese, and at high temperatures. Stay stable underneath.
The formed protective film is not easy to decompose at high temperatures, effectively preventing manganese from dissolution, significantly improving the high-temperature cycling performance of the battery, and optimizing the dynamic process and overall performance of the battery.
Smart Images

Figure CN119447469A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte additive, an electrolyte and a battery. Background Art
[0002] Lithium manganese oxide (LiMn2O4) is widely considered to be a promising cathode material for lithium-ion batteries due to its low cost, environmental protection and high voltage platform. However, its Jahn-Teller effect leads to structural distortion, which in turn affects the cycle performance. At the same time, the hydrofluoric acid (HF) generated by the reaction of lithium salt LiPF6 in the electrolyte with trace H2O will accelerate the dissolution of manganese, resulting in significant capacity decay of the battery during the cycle, especially under high temperature conditions, the dissolution of manganese is accelerated, further reducing the high temperature performance of lithium manganese oxide.
[0003] Research in recent years has shown that by adding specific additives to the electrolyte to improve the solid electrolyte interface of the battery, the dissolution of manganese can be effectively inhibited, thereby improving the performance of lithium manganese oxide batteries. However, although the existing electrolyte film-forming additives can form a CEI film on the positive electrode surface, these CEI films are easily decomposed at high temperatures and cannot effectively prevent the dissolution of manganese, resulting in poor high-temperature cycle performance of the battery.
[0004] Therefore, there is an urgent need for an electrolyte additive, an electrolyte and a lithium manganate lithium ion battery for solving the above problems. Summary of the invention
[0005] In view of this, the present invention discloses an electrolyte additive, an electrolyte and a battery, which improve the protection of the positive electrode at high temperature, thereby helping to improve the high temperature cycle performance of the battery. The technical solution of the present invention is implemented as follows:
[0006] The first aspect of the present invention discloses an electrolyte additive, comprising a first additive; the first additive comprises a compound represented by formula (1):
[0007]
[0008] Wherein, m and n are integers, and 1≤m≤20, 1≤n≤20, R1 and R2 include any one of a halogen substituent, a substituted or unsubstituted alkyl group, and the R1 or the R2 is the substituted or unsubstituted alkyl group, and the number of carbon atoms in the alkyl group is not greater than 5.
[0009] Specifically, the first additive is selected from one or more compounds represented by formula (1-1), formula (1-2), formula (1-3) and formula (1-4):
[0010]
[0011] Optionally, based on the total mass of the electrolyte, the mass ratio of the first additive to the electrolyte is 0.5% to 2.5%.
[0012] Specifically, a second additive is also included, and the second additive includes at least one of fluoroethylene carbonate, vinylene carbonate, methylene methanedisulfonate, succinic anhydride, and vinyl sulfate.
[0013] Optionally, based on the total mass of the electrolyte, the mass ratio of the second additive to the electrolyte is 1% to 4%.
[0014] Optionally, the second additive further includes a lithium salt additive, wherein the lithium salt additive includes one or more of lithium difluorooxalatoborate, lithium difluorophosphate, and lithium dioxalatoborate.
[0015] Optionally, based on the total mass of the electrolyte, the mass ratio of the lithium salt additive to the electrolyte is 0.1% to 1%.
[0016] Optionally, the electrolyte additive further includes a film-forming aid, and the film-forming aid includes at least one of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, 1,3-propane sultone, ethylene vinyl sulfite, and vinyl sulfite.
[0017] Optionally, based on the total mass of the electrolyte, the mass ratio of the film-forming aid to the electrolyte is 0.5% to 2%.
[0018] The second aspect of the present invention discloses an electrolyte, comprising: the above electrolyte additive, a lithium salt electrolyte, and a solvent, wherein the electrolyte additive accounts for 1 to 7% of the electrolyte by mass.
[0019] Optionally, the solvent is selected from one or more of carbonate, carboxylate, ether or sulfone compounds.
[0020] Optionally, the carbonate includes one or more of propylene carbonate, ethylene carbonate, butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate;
[0021] Optionally, the carboxylic acid ester includes one or more of γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, propyl formate, ethyl propionate and propyl propionate;
[0022] Optionally, the ethers include one or more of dioxolane, 1.2-dimethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran;
[0023] Optionally, the sulfone compound includes one or more of dimethyl sulfoxide and sulfolane.
[0024] Optionally, the lithium salt electrolyte includes one or more of lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)methyl lithium, lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
[0025] The third aspect of the present invention discloses a battery, comprising: the above-mentioned electrolyte, a manganese-based positive electrode, a negative electrode, and a separator arranged between the manganese-based positive electrode and the negative electrode.
[0026] The advantages of the present invention are as follows:
[0027] (1) The protective film formed by the present invention is not easy to decompose at high temperature, effectively prevents the dissolution of manganese, has good stability at high temperature, and significantly improves the high temperature cycle performance of the battery.
[0028] (2) The coordination of the quaternary ammonium group and the sulfonate group of the above-mentioned compound in the present invention improves the film-forming effect, further inhibits the generation of gas, and is beneficial to the high-temperature cycle performance of the battery. In addition, the compound molecule can react with H + Reacting with HF reduces the corrosion of these components to the protective film, making the protective film more stable in a high temperature environment.
[0029] (3) The first additive in the present invention has a strong coordination ability and can complex the transition metal Mn 2+ At the same time, the molecular structure characteristics of the compound can prevent Mn 2+ Dissolve again to reduce the occurrence of side reactions, and use with film-forming aids to form a more uniform and dense protective film, accelerate the transmission of lithium ions, optimize the battery's kinetic process, and greatly improve the battery's cycle stability and overall performance. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0032] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0033] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0034] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0035] It should be noted that, for the convenience of description, in the following embodiments, all identical technical features are marked with the same symbols.
[0036] The embodiments of the present invention will be described in more detail below by way of examples. It should be noted that the embodiments of the present invention are not limited to these examples.
[0037] The first aspect of the present invention discloses an electrolyte additive, comprising a first additive, wherein the first additive comprises a compound represented by formula (1):
[0038]
[0039] Wherein, m and n are integers, and 1≤m≤20, 1≤n≤20, R1 and R2 include any one of a halogen substituent, a substituted or unsubstituted alkyl group, R1 or R2 is a substituted or unsubstituted alkyl group, and the number of carbon atoms in the alkyl group is not greater than 5.
[0040] In some embodiments, m and n can be 1, 2, 3, 4, 5, 6, 7, ..., 16, 17, 18, 19, 20, respectively.
[0041] In some embodiments, R1 and R2 can be halogen substituents, for example, R1 and R2 can be independently selected from -F, -Cl, -Br, -I and the like.
[0042] In some embodiments, R1 and R2 can be independently selected from unsubstituted alkyl groups, such as straight-chain alkyl groups such as -CH3, -CH2CH3, -(CH2)2CH3, -(CH2)3CH3, -(CH2)4CH3, or branched alkyl groups such as -CH(CH3)2 and -C(CH3)3.
[0043] In some embodiments, R1 and R2 can be selected from substituted alkyl groups, respectively, wherein the substituents can be selected from halogen groups such as -F, -Cl, -Br, -I, or other functional groups such as -OH, -COOH, -COOR, aromatic groups, alkenyl groups, alkynyl groups, etc., and of course, alkyl substituents can also be selected.
[0044] The above selection of R1 and R2 is only for illustrative purposes and is not intended to be limiting. In practical applications, reasonable selection can be made according to requirements.
[0045] In the present invention, the first additive comprises a lithium compound represented by formula (1), wherein the molecule of the compound comprises a sulfonate group and a quaternary ammonium group; wherein the sulfonate group can participate in the formation of a positive electrode and a negative electrode surface protective film, and the quaternary ammonium group and the sulfonate group cooperate to promote the formation of a positive and negative electrode surface protective film, thereby reducing the effect of manganese dissolution on the negative electrode SEI film and improving the stability of the battery during the cycle; at the same time, the sulfonate group can inhibit the formation of gas and improve the high temperature performance of the battery, and the quaternary ammonium group in the compound can enhance the activity of the sulfonate group, thereby enhancing its film-forming effect and the ability to inhibit gas production.
[0046] On the other hand, the lithium compound contained in the first additive is a Lewis base, which can react with H+ and the harmful component HF to undergo an acid-base neutralization reaction, thereby weakening the corrosion of HF on the surface film, thereby further improving the high temperature resistance of the protective film; the protective film produced by the synergistic effect of the quaternary ammonium group and the sulfonate group is also more uniform and dense, improving the resistance of the protective film to H+ and HF corrosion. In addition, the quaternary ammonium group and the sulfonate group in the molecule are connected by an alkyl chain (-CH2-), so that during the use of the battery, the film-forming effect of the sulfonate group continues, the protective film is continuously repaired, and the gas production is continuously suppressed, thereby making the electrolyte have better high temperature cycle performance.
[0047] Furthermore, the lithium compound contained in the first additive has a strong coordination ability and can complex the transition metal Mn2+. The presence of R1, R2 and side chains such as alkyl chains in the molecular formula makes it difficult for the Mn2+ complexed in the protective film to be released again, which not only inhibits the side reactions of the transition metal catalytic oxidation electrolyte, but also slows down the loss of active lithium caused by the deposition of transition metals at the negative electrode, thereby improving the cycle stability of the battery.
[0048] In some embodiments, the first additive is selected from one or more compounds represented by formula (1-1), formula (1-2), formula (1-3) and formula (1-4):
[0049]
[0050]
[0051] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the first additive to the electrolyte is 0.5% to 2.5%. The electrolyte additive of the present application has a more stable high-temperature performance of the protective film formed under the above mass ratio, and can still maintain good high-temperature cycle performance without the joint action of other additives or auxiliary agents.
[0052] Specifically, the mass ratio of the first additive to the electrolyte can be 0.5%, 0.7%, 0.9%, 1.0%, 1.3%, 1.5%, 1.7%, 1.9%, 2.0%, 2.3%, 2.5%, etc., but is not limited to this. In actual application, a reasonable choice can be made according to needs.
[0053] In some embodiments, the electrolyte additive further includes a second additive, and the second additive includes at least one of fluoroethylene carbonate, vinylene carbonate, methylene methanedisulfonate, succinic anhydride, and vinyl sulfate.
[0054] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the second additive to the electrolyte is 1% to 4%.
[0055] Specifically, the mass ratio of the second additive to the electrolyte can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, etc., but is not limited thereto. In actual applications, a reasonable selection can be made according to needs.
[0056] In some preferred embodiments, the mass ratio of the second additive B to the first additive A is (5-10):(1-2).
[0057] In the present application, the second additive acts synergistically with the first additive, and a denser and more stable protective film can be formed under the above-mentioned mass ratio, and the high-temperature performance of the battery is more stable.
[0058] In some embodiments, the second additive further includes a lithium salt additive, wherein the lithium salt additive includes one or more of lithium difluorooxalatoborate, lithium difluorophosphate, and lithium dioxalatoborate.
[0059] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the lithium salt additive to the electrolyte is 0.1% to 1%.
[0060] Specifically, the mass ratio of lithium salt additive to electrolyte can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., but it is not limited to this. In actual application, it can be reasonably selected according to needs.
[0061] In some preferred embodiments, the mass ratio of the lithium salt additive to the first additive is (1-2):
[0062] (1~3).
[0063] In the present application, the addition of lithium salt further enhances the film-forming effect of the second additive on the first additive.
[0064] In some embodiments, the electrolyte additive further includes a film-forming aid, and the film-forming aid includes at least one of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, 1,3-propane sultone, ethylene vinyl sulfite, and vinyl sulfite.
[0065] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the film-forming aid to the electrolyte is 0.5% to 2%.
[0066] Specifically, the mass ratio of lithium salt additive to electrolyte can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc., but is not limited to this. In actual application, it can be reasonably selected according to needs.
[0067] In some preferred embodiments, the film-forming aid is selected from at least one of tris(trimethylsilyl)phosphate (TMSP) and tris(trimethylsilyl)borate (TMSB). In the above configuration, the trimethylsilyl group, phosphate group and borate group in TMSP and TMSB can promote the film formation of the first additive.
[0068] Through the above arrangement, the first additive, the second additive and the film-forming aid provided by the present invention can form a uniform and dense protective film on the surface of the positive and negative electrodes of the battery. The presence of the protective film can prevent the direct contact between the positive and negative electrode surfaces and the electrolyte, thereby reducing the degree of side reactions. At the same time, the protective film can help to quickly transmit lithium ions and accelerate the kinetic process of the battery. The combination of the three can also act on the manganese-based positive electrode material of the battery system, slowing down the crystal structure distortion and interface side reactions caused by the dissolution of transition metals. At the same time, the multi-functional groups of the first additive, the second additive and the film-forming aid can synergistically act on the battery system, which has a positive effect on the high temperature storage performance and cycle performance of the battery.
[0069] The second aspect of the present invention discloses an electrolyte, comprising: the above electrolyte additive, a lithium salt electrolyte, and a solvent, wherein the electrolyte additive accounts for 1 to 7% of the electrolyte by mass.
[0070] Specifically, the mass ratio of the first additive to the electrolyte can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, etc., but is not limited to this. In actual application, a reasonable choice can be made according to needs.
[0071] In some embodiments, the solvent is selected from one or more of carbonate, carboxylate, ether or sulfone compounds.
[0072] In some embodiments, the carbonate includes one or more of propylene carbonate, ethylene carbonate, butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
[0073] In some embodiments, the carboxylic acid ester includes one or more of gamma-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, propyl formate, ethyl propionate, and propyl propionate.
[0074] In some embodiments, the ethers include one or more of dioxolane, 1,2-dimethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran.
[0075] In some embodiments, the sulfone compound includes one or more of dimethyl sulfoxide and sulfolane.
[0076] In some embodiments, the lithium salt electrolyte includes one or more of lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl lithium, lithium bis(oxalatoborate) and lithium difluorooxalatoborate. The above lithium salt electrolyte has better compatibility with the electrolyte additive of the present application and has better film-forming effect on the electrolyte additive.
[0077] In other embodiments, the lithium salt electrolyte may also be selected from lithium iodide, lithium bromide, lithium thiocyanate, lithium tetraphenylborate, lithium tetrafluorooxalate phosphate, lithium nitrate, lithium hexafluoroarsenate, lithium fluoroalkylphosphonate, lithium phosphate, and combinations thereof.
[0078] The third aspect of the present invention discloses a battery, comprising: the above-mentioned electrolyte, a manganese-based positive electrode, a negative electrode, and a separator arranged between the manganese-based positive electrode and the negative electrode.
[0079] In some embodiments, the manganese-based positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. Further, the positive electrode active material layer includes positive electrode active material particles, a positive electrode conductive agent, a positive electrode binder or other additives.
[0080] In some embodiments, the manganese-based positive electrode can be prepared by a wet process or a dry process.
[0081] The dry process is to dry-mix the positive electrode active particles, positive electrode conductive agent and adhesive, and then fibrillate the mixture to form a self-supporting film under the fibrillation of the positive electrode adhesive, and finally roll it to cover the surface of the positive electrode current collector. Fibrillation film making is the front link of the electrode rolling. The mainstream fibrillation film making machines are: 1) air flow mill; 2) screw extruder; 3) open mill. After the binder and active material are fully mixed, the mixture is sent to the fibrillation film making machine, and the mixture will form a self-supporting film under the rolling of the machine.
[0082] The wet process is to add a solvent (such as NMP) to the positive electrode active particles, positive electrode conductive agent and adhesive for homogenization, apply the homogenized slurry to the surface of the positive electrode collector through a coater, and form a positive electrode sheet after drying.
[0083] The manganese-based positive electrode material can be selected from one or more of lithium manganese oxide, lithium nickel manganese oxide, and lithium iron manganese phosphate, or can be a mixture of one or more of the above manganese-based positive electrode materials and non-manganese-based materials.
[0084] The positive electrode current collector may be a metal foil, metal grid or mesh, or mesh metal comprising aluminum or any other suitable conductive material known to those skilled in the art.
[0085] In some embodiments, in order to further improve the lithium ion transport performance of the battery, solid electrolyte particles may be added to the positive electrode active material layer.
[0086] In various aspects, as described above, the electrolyte can be a solid electrolyte, which can include one or more solid electrolyte particles. Preferably, solid electrolyte particles can also be added to the negative electrode, and the solid electrolyte particles can include one or more polymer components, oxide particles, sulfide particles, halide particles, borate particles, nitride particles or hydride particles.
[0087] As an embodiment, the polymer-based component may include one or more polymer materials selected from the group consisting of polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene oxide) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof. In one variation, the one or more polymer materials may have an ionic conductivity equal to about 10-4 S / cm.
[0088] As an implementation, the oxide particles may include one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li6.5La3Zr1.75Te0.25O12, Li7La3Zr2O12, Li6.2Ga0.3La2.95Rb0.05Zr2O12, Li6.85La2.9Ca0.1Zr1.75Nb0.25O12, Li6.25Al0.25La3Zr2O12, Li6.75La3Zr1.75Nb0.25O12, Li6.75La3Zr1.75Nb0.25O12, and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li14Zn(GeO4)4, Li3+x(P1-xSix)O4 (where 0 < x < 1), Li3+xGexV1-xO4 (where 0 < x < 1), and combinations thereof. One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li1+xAlxGe2-x(PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li1+xAlxTi2-x(PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li1+xYxZr2-x(PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li1.3Al0.3Ti1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. One or more perovskite ceramics may be selected from the group consisting of: Li3.3La0.53TiO3, LiSr1.65Zr1.3Ta1.7O9, Li2x-ySr1-xTayZr1-yO3 (where x = 0.75y and 0.60 < y < 0.75), Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3, Li3xLa(2 / 3-x)TiO3 (where 0 < x < 0.25), and combinations thereof. In one variation, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10-5 S / cm to less than or equal to about 10-1 S / cm.
[0089] In various aspects, the sulfide-based particles can include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MSx (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li3.4Si0.4P0.6S4, Li10GeP2S11.7O0.3, Li9.6P3S12, Li7P3S11, Li9P3S9O3, Li10.35Si1.35P1.65S12, Li9.81Sn0.81P2.19S12, Li10(Si0.5Ge0.5)P2S12, Li(Ge0.5Sn0.5)P2S12, Li(Si0.5Sn0.5)PsS12, Li10GeP2S12 (LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li10.35Ge1.35P1.65S12, Li3.25Ge0.25P0.75S4, Li10SnP2S12, Li10SiP2S12, Li9.54Si1.74P1.44S11.7Cl0.3, (1-x)P2S5-xLi2S (where 0.5 ≤ x ≤ 0.7), and combinations thereof. In one variant, the one or more sulfide-based materials can have an ionic conductivity greater than or equal to about 10-7 S / cm to less than or equal to about 1 S / cm.
[0090] In various aspects, the halide-based particles can include one or more halide-based materials selected from the group consisting of: Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl1-xBrx (where 0 < x < 1), and combinations thereof. In one variant, the one or more halide-based materials can have an ionic conductivity greater than or equal to about 10-8 S / cm to less than or equal to about 10-1 S / cm.
[0091] In various aspects, the borate-based particles can include one or more borate-based materials selected from the group consisting of: Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variant, the one or more borate-based materials can have an ionic conductivity greater than or equal to about 10-7 S / cm to less than or equal to about 10-2 S / cm.
[0092] In various aspects, the nitride-based particles may include one or more nitride-based materials selected from the group consisting of Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variation, the one or more nitride-based materials may have an ionic conductivity of greater than or equal to about 10-9 S / cm to less than or equal to about 1 S / cm.
[0093] In various aspects, the hydride-based particles may include one or more hydride-based materials selected from the group consisting of Li3AlH6, LiBH4, LiBH4-LiX (wherein X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4-LiNH2, and combinations thereof. In one variation, the one or more hydride-based materials may have an ionic conductivity of greater than or equal to about 10-7 S / cm to less than or equal to about 10-2 S / cm.
[0094] The positive electrode binder may be selected from polytetrafluoroethylene (PTFE), sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), and combinations thereof.
[0095] The positive electrode conductor may include carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, superP, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, etc.
[0096] The positive electrode may include greater than or equal to about 50 wt % to less than or equal to about 97 wt % of a positive electrode active material, optionally greater than or equal to about 0 wt % to less than or equal to about 15 wt % of a positive electrode conductive material, and optionally greater than or equal to about 0 wt % to less than or equal to about 10 wt % of a positive electrode binder.
[0097] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. Further, the negative electrode active material layer includes negative electrode active material particles, a negative electrode conductive agent, a negative electrode binder or other additives.
[0098] In some embodiments, the negative electrode can be prepared by a wet method or a dry method. The dry process of the negative electrode is to dry-mix the negative electrode active particles, the negative electrode conductive agent and the negative electrode binder, and then fibrillate the mixture to form a self-supporting film under the fibrillation of the negative electrode binder, and finally roll and cover the surface of the negative electrode sheet current collector. The wet process is to add a solvent (such as NMP) to the negative electrode active particles, the negative electrode conductive agent and the negative electrode binder for homogenization, and apply the homogenized slurry to the surface of the negative electrode current collector through a coating machine, and form a negative electrode sheet after drying.
[0099] The negative electrode current collector may be a metal foil, metal grid or mesh, or mesh metal comprising copper or any other suitable conductive material known to those skilled in the art.
[0100] The negative electrode is formed of a lithium main body material that can be used as a negative terminal of a lithium ion battery. For example, the negative electrode may include a lithium main body material (e.g., a negative electrode active material) that can be used as a negative terminal of a battery. In various aspects, the negative electrode may be defined by a variety of negative electrode active material particles. Such negative electrode active material particles may be arranged in one or more layers to define the three-dimensional structure of the negative electrode. In some variations, the negative electrode may also include an electrolyte, such as a variety of electrolyte particles, and the electrolyte particles may be inorganic solid electrolyte particles, such as sulfide electrolyte particles, halide electrolyte particles, oxide electrolyte particles, hydride electrolyte particles, expanded electrolyte particles, etc., or may be a polymer electrolyte, such as polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO) or polyvinylidene chloride (PVDC), etc.
[0101] The negative electrode may include a lithium-based negative electrode active material, which includes, for example, lithium metal and / or a lithium alloy. In other embodiments, the negative electrode is a silicon-based negative electrode active material, which includes silicon, such as a silicon alloy, silicon oxide, or a combination thereof, which may also be mixed with graphite in some cases. In other embodiments, the negative electrode may include a carbonaceous-based negative electrode active material, which includes one or more of graphite, graphene, carbon nanotubes (CNTs), and combinations thereof. In yet another embodiment, the negative electrode includes one or more negative electrode active materials that accept lithium, such as lithium titanium oxide (Li4Ti5O12), one or more transition metals (e.g., tin (Sn)), one or more metal oxides (e.g., vanadium oxide (V2O5), tin oxide (SnO), titanium dioxide (TiO2)), titanium niobium oxide (TixNbyOz, wherein 0≤x≤2, 0≤y≤24, and 0≤z≤64), a metal alloy (such as, copper-tin alloy (Cu6Sn5)) and one or more metal sulfides (such as, iron sulfide (FeS)).
[0102] The positive electrode binder can be selected from polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate and combinations thereof.
[0103] The positive electrode conductor may include carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, superP, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, etc.
[0104] The negative electrode may include greater than or equal to about 50 wt % to less than or equal to about 97 wt % of a negative electrode active material, optionally greater than or equal to about 0 wt % to less than or equal to about 60 wt % of a solid electrolyte, optionally greater than or equal to about 0 wt % to less than or equal to about 15 wt % of a negative electrode conductive material, and optionally greater than or equal to about 0 wt % to less than or equal to about 10 wt % of a negative electrode binder.
[0105] In various cases, the separator can be a microporous polymer separator comprising a polyolefin, including a polyolefin made from a homopolymer (derived from a single monomer component) or a heteropolymer (derived from more than one monomer component), the homopolymer and heteropolymer can be linear or branched. In certain aspects, the polyolefin can be polyethylene (PE), polypropylene (PP), or a blend of PE and PP, or a multilayer structured porous film of PE and / or PP. Commercially available polyolefin porous separators include those available from Celgard LLC. 2500 (single-layer polypropylene diaphragm) and 2340 (three-layer polypropylene / polyethylene / polypropylene diaphragm).
[0106] When the separator is a microporous polymer separator, it can be a single layer or a multi-layer laminate. For example, in one embodiment, a single layer of polyolefin can form the entire microporous polymer separator. In other aspects, for example, the separator can be a fiber membrane having a large number of pores extending between opposing surfaces and can have a thickness of less than 1 mm. However, as another example, multiple discrete layers of similar or different polyolefins can be assembled to form the separator.
[0107] In place of or in addition to polyolefins, the microporous polymer separator may include other polymers such as, but not limited to, polyethylene terephthalate (PET), polyvinylidene fluoride (PVdF), polyamide (nylon), polyurethane, polycarbonate, polyester, polyetheretherketone (PEEK), polyethersulfone (PES), polyimide (PI), polyamide-imide, polyether, polyoxymethylene (e.g., acetal), polybutylene terephthalate, polyethylenenaphthenate, polybutylene, polymethylpentene, polyolefin copolymers, propylene nitrile-butadiene-styrene copolymers (ABS), polystyrene copolymers, polymethyl methacrylate (PMMA), polysiloxane polymers (e.g., polydimethylsiloxane (PDMS)), polybenzimidazole (PBI), polybenzoxazole (PBO), polyphenylene, polyarylene ether ketone, polyperfluorocyclobutane, polyvinylidene fluoride copolymers (e.g., PVdF-hexafluoropropylene or (PVdF-HFP)) and polyvinylidene fluoride terpolymers, polyvinyl fluoride, liquid crystal polymers (e.g., VECTRAN™ (Hoechst AG, Germany) and (DuPont of Wilmington, Del.), polyaramid, polyphenylene ether, cellulosic material, mesoporous silica, or a combination thereof.
[0108] In addition, the separator may also be mixed with a ceramic material, or its surface may be coated with a ceramic material. For example, the ceramic coating may include aluminum oxide (Al2O3), silicon dioxide (SiO2), or a combination thereof. Various conventionally available polymers and commercial products for forming the separator are contemplated, as well as many manufacturing methods that may be employed to manufacture such a multi-microporous polymer separator.
[0109] The electrolyte was prepared as follows:
[0110] The preparation conditions of the electrolytes of Examples 1-10 and Comparative Examples 1-4 are: the electrolytes are prepared in a glove box filled with high-purity argon gas, the environmental conditions of the glove box are O2≤0.01ppm, H2O≤0.01ppm, the raw materials involved in the preparation of the electrolytes are all battery grade, and the raw materials are subjected to conventional operating steps such as dehydration and drying before preparation.
[0111] Example 1
[0112] First, add LiPF6 in an amount of 12% by weight of the electrolyte to the organic solvent system, and after it is completely dissolved, add the first additive in an amount of 1% by weight of the electrolyte, stir evenly and fully dissolve to obtain an electrolyte;
[0113] The first additive is a compound represented by the following formula:
[0114]
[0115] Example 2
[0116] First, add LiPF6 at a ratio of 12% by mass of the electrolyte to the organic solvent system, and after it is completely dissolved, add the second additive at a ratio of 1% by mass of the electrolyte, and then add the first additive at a ratio of 1% by mass of the electrolyte. After stirring evenly and dissolving fully, an electrolyte is obtained.
[0117] The first additive is a compound represented by the following formula:
[0118]
[0119] The second additive was 2% EFC.
[0120] Example 3
[0121] First, add LiPF6 at a ratio of 12% by mass of the electrolyte to the organic solvent system. After it is completely dissolved, add the second additive and the film-forming additive at a ratio of 4% and 2% by mass of the electrolyte respectively. Subsequently, add the first additive at a ratio of 1% by mass of the electrolyte, stir evenly and dissolve fully to obtain the electrolyte.
[0122] The first additive is a compound represented by the following formula:
[0123]
[0124] The second additive is 2% VC + 2% EFC;
[0125] The film-forming additive was 2% TMSP.
[0126] Example 4
[0127] The preparation method of the electrolyte is the same as that of Example 3, except that the second additive is 2% VC+1.5% EFC+0.5% LiPO2F2, and the film-forming aid is 0.5% TMSP.
[0128] Example 5
[0129] The preparation method of the electrolyte is the same as that of Example 3, except that the second additive is 2% VC+1.5% EFC+0.5% LiBOB, and the film-forming aid is 1% TMSP.
[0130] Example 6
[0131] The electrolyte preparation method is the same as that of Example 3, except that the mass ratio of the first additive is 2.5%, the second additive is 2% VC+1.5% EFC+0.5% LiPO2F2, and the film-forming aid is 1% TMSB.
[0132] Example 7
[0133] The preparation method of the electrolyte is the same as that of Example 3, except that the mass ratio of the first additive is 0.5%, the second additive is 2% VC+1.5% EFC+0.5% LiBOB, and the film-forming aid is 1% TMSB.
[0134] Example 8
[0135] The preparation method of the electrolyte is the same as that of Example 3, except that the second additive is 1% VC+0.5% EFC+0.1% LiDFOB, and the film-forming aid is 0.8% TMSP+0.5% VES.
[0136] Example 9
[0137] The preparation method of the electrolyte is the same as that of Example 3, except that the second additive is 2% VC+1.5% EFC+1% LiDFOB, and the film-forming aid is 0.8% TMSP+0.5% PS.
[0138] Example 10
[0139] The electrolyte preparation method is the same as that of Example 3, except that the mass ratio of the first additive is 0.3%, the second additive is 3% VC+2% EFC+1% LiPO2F2, the film-forming aid is 0.5% TMSP+0.5% TMSB, and the lithium salt is LiFSI.
[0140] Comparative Example 1
[0141] First, add LiPF6 in an organic solvent system at a ratio of 12% by weight of the electrolyte, and after it is completely dissolved, add the second additive and the film-forming agent, and stir evenly and fully dissolve to obtain the electrolyte;
[0142] The second additive is 2% VC+1% EFC+0.5% LiPO2F2, and the film-forming agent is 0.5% DTD.
[0143] Comparative Example 2
[0144] The method is the same as that of Comparative Example 1, except that the second additive is 2% VC+1% EFC+0.5% LiPO2F2, and the film-forming agent is 1.0% PS+0.5% DTD.
[0145] Comparative Example 3
[0146] The method is the same as that of Comparative Example 1, except that the second additive is 2% VC+1% EFC+1.0% LiBOB, and the film-forming agent is 0.5% VES.
[0147] Comparative Example 4
[0148] The method is the same as that of Comparative Example 1, except that the second additive is 2% VC+1% EFC+1.0% LiBOB, and the film former is 1.0% PS+0.5% VES.
[0149] Among them, the solvent system of Examples 1 to 4, 6, 8 to 10 and Comparative Examples 1 to 2 is (ethylene carbonate) EC: (ethyl methyl carbonate) EMC: (diethyl carbonate) DEC = 3:4:3, and the solvent system of Examples 5, 7 and Comparative Examples 3 to 4 is (ethylene carbonate) EC: (ethyl methyl carbonate) EMC: (diethyl carbonate) DMC = 3:4:2:1. The above ratios are all volume ratios. In addition, the amount of organic solvent used wt.% = 100wt.% - lithium salt electrolyte wt.% - second additive wt.% - first additive wt.% - film-forming aid wt.%.
[0150] The present invention combines and matches the additive content within the preferred range, and conducts a DOE experiment on the additive combination method. The test results are shown in Table 1 below:
[0151] Table 1
[0152]
[0153] The results show that Example 5 is the optimal combination. The electrolyte solution for a manganese-based battery provided in the present application can achieve excellent room temperature cycle and high temperature cycle performance, and is more conducive to improving the battery cycle performance and life. According to the comparison between Examples 2-10 and Example 1, the use of the second additive and the first additive together improves the room temperature cycle and high temperature cycle performance of the battery, especially when the film-forming additive includes TMSP or TMSB, the room temperature cycle and high temperature cycle performance of the battery are excellent, and the addition of lithium salt additives also improves the room temperature cycle and high temperature cycle performance of the battery.
[0154] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte additive, characterized in that: Including a first additive; the first additive includes a compound represented by formula (1): Wherein, m and n are integers, and 1≤m≤20, 1≤n≤20; R1 and R2 include any of a halogen substituent, a substituted or unsubstituted alkyl group; The R1 or the R2 is the substituted or unsubstituted alkyl group, and the number of carbon atoms in the alkyl group is not greater than 5.
2. An electrolyte additive according to claim 1, characterized in that: The first additive is selected from one or more compounds represented by formula (1-1), formula (1-2), formula (1-3) and formula (1-4):
3. An electrolyte additive according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass ratio of the first additive to the electrolyte is 0.5% to 2.5%.
4. The electrolyte additive according to claim 1, characterized in that: It also includes a second additive, which includes at least one of fluoroethylene carbonate, vinylene carbonate, methylene methanedisulfonate, succinic anhydride, and vinyl sulfate; based on the total mass of the electrolyte, the mass ratio of the second additive to the electrolyte is 1% to 4%.
5. An electrolyte additive according to claim 4, characterized in that: The second additive also includes a lithium salt additive, wherein the lithium salt additive includes one or more of lithium difluorooxalatoborate, lithium difluorophosphate, and lithium dioxalatoborate; based on the total mass of the electrolyte, the mass ratio of the lithium salt additive to the electrolyte is 0.1% to 1%.
6. The electrolyte additive according to claim 1, characterized in that: The electrolyte additive also includes a film-forming aid, which includes at least one of tri(trimethylsilyl) phosphate, tri(trimethylsilyl) borate, 1,3-propane sultone, ethylene vinyl sulfite, and vinyl sulfite; based on the total mass of the electrolyte, the mass ratio of the film-forming aid to the electrolyte is 0.5% to 2%.
7. An electrolyte comprising: The electrolyte additive, lithium salt electrolyte, and solvent according to any one of claims 1 to 5, wherein the electrolyte additive accounts for 1 to 7% of the electrolyte by mass.
8. An electrolyte according to claim 7, characterized in that: The solvent is selected from one or more of carbonate, carboxylate, ether or sulfone compounds; Wherein, the carbonate includes one or more of propylene carbonate, ethylene carbonate, butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; The carboxylic acid ester includes one or more of γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, propyl formate, ethyl propionate and propyl propionate; The ethers include one or more of dioxolane, 1.2-dimethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; The sulfone compound includes one or more of dimethyl sulfoxide and sulfolane.
9. An electrolyte according to claim 7, characterized in that: The lithium salt electrolyte includes one or more of lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)methyl lithium, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
10. A battery, characterized in that: include: The electrolyte according to any one of claims 7 to 9, a manganese-based positive electrode, a negative electrode, and a separator disposed between the manganese-based positive electrode and the negative electrode.